Biological, Behavioural and Spurious Selection on the Kidney Transplant Waitlist - Stephen Kastoryano (Institute of Labor Economics (IZA), 2024)
The kidney allocation system aims to distribute kidneys from deceased donors in an equitable and potential-life optimising manner. This is a difficult task, not least because intrinsic biological differences, such as a person's ABO blood type, influence the allocation. This paper begins by presenting a curious and undocumented empirical fact: candidates on the kidney transplant waitlist with blood types implying they will more rapidly be offered a kidney display lower pre-transplant survival. The paper investigates whether this difference in pre-transplant survival is due to biological, behavioural, or spurious selection. To that end, we promote a two-in-one randomization design which allows us to credibly fit our empirical setting within a dynamic potential outcomes framework. Using this framework, drawing from economic theory, and noting problematic financial and legal market incentives, the paper systematically evaluates different explanations for pre-transplant survival patterns. Our analysis establishes a small set of behavioural explanations which directly inform debates about how to reduce the excessive discard of viable kidneys in the US transplant market.
Keywords: I12; I18; C22; C41; 330; kidney transplant; expectation effects; dynamic treatment effects; survival models